Caracterização e atividade antimicrobiana de emulsões à base de óleo da polpa de pequi (Caryocar brasiliense) para o desenvolvimento de um cicatrizante tópico - Pereira, Tácio Fragoso (2022)
The search for new pharmaceutical formulations of natural and sustainable origin, which present a broad spectrum of biological properties capable of optimizing wound repair and healing, has been a current focus of investigations. Among the fruit trees of the Brazilian Cerrado, with strong potential for sustained exploitation, is the pequi (Caryocar brasiliense), from which the oil from the pequi pulp (OP) is extracted. In the present study, emulsified formulations containing 1, 3 and 5% (p/p) of pequi pulp oil with and without carboxymethylcellulose (CMC) at 1% (p/p) and 8% (p/p) Tween 80 were prepared using a high speed rotary mechanical shaker and characterized in order to evaluate their stability and potential antimicrobial activity. The first step of this study was the characterization of the oil from the pequi pulp using Fourier transform infrared spectroscopy (FTIR) and gas chromatography coupled to mass spectrometry (GC-MS). Their results indicated the presence of chemical groups characteristic of the oil itself and the presence in high proportion of fatty acids, essential in the process of tissue repair, respectively. In the macroscopic evaluation, all emulsions behaved stable throughout the evaluation period, estimated at 120 days, presenting slightly acidic values (pH) in the range of 4.10 - 4.89 for EOP and 6.50 - 6.89 for EOP+CMC; values compatible with skin. Mean hydrodynamic diameter (HD) less than 330 nm and polydispersity index (PDI) averaged around 0.3, indicating systems with low polydispersity. The Zeta potential (ζ) exhibited negative values, sufficient to stabilize the emulsified systems. The images obtained by scanning electron microscopy (SEM) showed that the EOP1+CMC emulsion exhibited micelle-like structures with smaller, uniform and well distributed sizes when compared to the other formulations. In the rheological result, all emulsions behaved as non-newtonian fluids, presenting thixotropic characteristics, considered important for applications in topical pharmaceutical formulations. The antimicrobial activity did not show the formation of inhibition halos for either the pure pequi pulp oil or the emulsified formulations (EOP+CMC) against the three strains under study (Staphylococcus aureus, Enteric Salmonella and Candida albicans). Although in the present study, antimicrobial activity was not evidenced, the pequi pulp oil presents in its composition relevant bioactive compounds that provide essential benefits for maintaining the integrity of the skin as well as in the regeneration and healing process of cutaneous wounds, revealing themselves as potentially useful for cosmetic and/or pharmaceutical purposes. In this sense, further investigations are suggested as in vivo tests of these formulations, to evaluate their biological response in the process of wound healing.